« Pèlerinage aux lieux saints » des animés et « regard touristique » : l’exemple de la série Hyōka et la ville de Takayama - Shin.ya Sutō (Ebisu: Études Japonaises)
The act of fans visiting locations depicted in anime is referred to in Japan as a “pilgrimage to sacred sites” (seichi junrei), a phenomenon that came to public attention during the late 2000s. In the case of the anime Hyōka, released in 2012 and examined in this paper, the story is set in Takayama, a tourist hot spot known for its historic streets. However, rather than viewing the city from the perspective of the tourist, the anime focuses on seemingly ordinary places and the everyday lives of the high school protagonists. Consequently, one can argue that the “pilgrims” of this anime arrive in search of the “real” Takayama, rather than Takayama the tourist destination. In fact, as this paper suggests, anime pilgrimages serve as a way to both visit a location as a tourist, and to “package” it as an “authentic” local experience.